Optimized speed controller for induction motor drive using quantum lightning search algorithm - Ali J.A.; Hannan M.A.; Mohamed A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric drives; Errors; Induction motors; Learning algorithms; Lightning; Mean square error; Optimization; Particle swarm optimization (PSO); Proportional control systems; Speed; Speed control; Backtracking search algorithms; MATLAB/Simulink environment; PI Controller; Proportional integral derivative controllers; Search Algorithms; Three phase induction motor; Trial-and-error procedures; V/f control; Controllers